2010
DOI: 10.1111/j.1600-048x.2009.04751.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative influence of male and female care in determining nestling mass in a migratory songbird

Abstract: Biparental care is common in birds, with the allocation of effort being highly variable between the sexes. In most songbird species, the female typically provides the most care early in the breeding cycle with both parents providing care when provisioning young. Food provisioning should be directly related to offspring quality; however, the relative influence each parent has on offspring quality has rarely been assessed at the nest level. Consequently, we were interested in assessing the relative influence mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…2. Better measures of workload, for large numbers of known-individuals: over 15 years ago, Wright et al (1998) highlighted the fact that individual birds can adjust their workload during provisioning by not only varying nest visit rate but also by varying load size, prey type, size, and nutritional content, foraging distance, travel time to and from the nest, and even costs of specific activities during foraging in food patches (see also Stodola et al 2010). Nevertheless, the simplest and most commonly used measure of parental effort continues to be the number of visits/unit time to the nest or per chick (correcting for brood size) as discussed above.…”
Section: Experimental Manipulation Of Workload In Free-livingmentioning
confidence: 98%
See 1 more Smart Citation
“…2. Better measures of workload, for large numbers of known-individuals: over 15 years ago, Wright et al (1998) highlighted the fact that individual birds can adjust their workload during provisioning by not only varying nest visit rate but also by varying load size, prey type, size, and nutritional content, foraging distance, travel time to and from the nest, and even costs of specific activities during foraging in food patches (see also Stodola et al 2010). Nevertheless, the simplest and most commonly used measure of parental effort continues to be the number of visits/unit time to the nest or per chick (correcting for brood size) as discussed above.…”
Section: Experimental Manipulation Of Workload In Free-livingmentioning
confidence: 98%
“…Nevertheless, the simplest and most commonly used measure of parental effort continues to be the number of visits/unit time to the nest or per chick (correcting for brood size) as discussed above. It is generally difficult to collect large amounts of data for many individuals on these other components of provisioning effort, but this is becoming easier with developments in nest cameras (García-Navas and Sanz 2010; Stodola et al 2010), RFID tags (Mariette et al 2011), automated radio-tracking systems that can cover relatively large areas of habitat (Mitchell et al 2012;Ryder et al 2012), or accelerometers Spivey and Bishop 2013). Thus, the goal should be to take a multivariate approach to obtain an integrated measurement of individual variation in parental workload coupled with physiological analysis of these same individuals.…”
Section: Experimental Manipulation Of Workload In Free-livingmentioning
confidence: 99%
“…Similarly, Schwagmeyer and Mock (2008) failed to find an association between parental deliveries and nestlings' mass, but they found that delivery of the largest food items predicted both the mass and probability of recruitment of nestlings. Thus the utility of measuring parental provisioning without taking into account prey quality could be called into question, as frequent feeding does not always guarantee that chicks are being nourished best (Grieco 2001, Tremblay et al 2005, Krist 2009, but see Stodola et al 2010).…”
Section: Parental Characteristics and Nestling Conditionmentioning
confidence: 99%
“…Female compensation for low male parental care has been demonstrated in a variety of species (Mutzel et al 2013), but has not often been simultaneously tied to plumage characteristics. Male provisioning rate has been demonstrated to be a more important predictor of nestling growth and survival than female provisioning rate, as it is more variable than female care (Stodola et al 2010). Indeed, in this study system across a larger number of nests (n ¼ 99), we found that male provisioning rate was a strong predictor of nestling growth rate after accounting for female provisioning rate (b ¼ 0.124, P ¼ 0.006).…”
Section: Discussionmentioning
confidence: 54%